Sexual risk behaviours and HIV seroprevalence among male sex workers who have sex with men and non-sex workers in Campinas, Brazil. Issue 6 (21st November 2008) - Tun, W; de Mello, M; Pinho, A; Chinaglia, M; Diaz, J
Abstract : Objectives: To compare population-based prevalence estimates of sexual risk behaviours and HIV seroprevalence of male sex workers who have sex with men (MSM) and those not engaged in sex work in Campinas, Brazil. Methods: MSM (n = 658) were recruited for a cross-sectional study through respondent-driven sampling. Audio-assisted computer self-interview was used to collect information on sexual behaviours and HIV testing (optional) was performed. Population-based prevalence estimates with 95% CI of characteristics and behaviours of MSM sex workers and non-sex workers are reported. Results: One-quarter reported ever receiving payment for sex and 14.8% (95% CI 11.1 to 19.0) had been paid in the previous 2 months; most exclusively with men. MSM sex workers were significantly more likely than non-sex workers to report being transgendered (40.5% vs 8.1%), to practise unprotected receptive (22.4% vs 4.6%) and insertive (20.5% vs 5.0%) anal intercourse with ⩾2 male partners and to have unprotected vaginal sex with women (22.7% vs 5.6%). MSM sex workers experienced significantly greater rates of psychological abuse (80.9% vs 58.4%) and physical abuse (48.2% vs 15.2%). Conclusions: MSM sex workers have higher sexual risk behaviours as well as social vulnerabilities than the general population of MSM. HIV/sexually transmitted infection prevention efforts should be targeted to this riskier subgroup. Programmes should be transgender sensitive, should recognise that MSM sex workers have sex with men and women and address other factors that influence risk, such as homophobic abuse.